2005
DOI: 10.1097/01.brs.0000160997.91502.3b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Healos/Bone Marrow to INFUSE(rhBMP-2/ACS) With a Collagen-Ceramic Sponge Bulking Agent as Graft Substitutes for Lumbar Spine Fusion

Abstract: From the manual palpation, radiographic and biomechanical assessment of fusion, the results in this study showed that INFUSE (rhBMP-2/collagen sponge) consistently produced spine fusion when wrapped around a collagen-ceramic sponge bulking agent (Mastergraft Matrix). Meanwhile, Healos was ineffective as a bone graft material when combined with heparinized autogenous bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 20 publications
(22 reference statements)
1
30
0
1
Order By: Relevance
“…Its osteoconductive function and qualification as a graft extender were shown in our previous clinical studies compared to those of the autogenous iliac bone graft in human posterolateral fusion of lumbar spine, which is consistent with results from other studies using synthetic hydroxyapatite in posterolateral fusion [13][14][15][16]. However, in interbody fusion, there are contradictory reports on the efficacy of synthetic hydroxyapatite as a graft extender [15][16][17].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Its osteoconductive function and qualification as a graft extender were shown in our previous clinical studies compared to those of the autogenous iliac bone graft in human posterolateral fusion of lumbar spine, which is consistent with results from other studies using synthetic hydroxyapatite in posterolateral fusion [13][14][15][16]. However, in interbody fusion, there are contradictory reports on the efficacy of synthetic hydroxyapatite as a graft extender [15][16][17].…”
Section: Introductionsupporting
confidence: 88%
“…However, it has a limitation as a graft material in that it acts purely as an osteoconductive scaffold and contains neither osteogenic cell nor osteoinductive factor. Hence in another published studies using a spongy-form synthetic hydroxyapatite bone it was recommended to be used in combination with adjuvant osteoinductive materials like bone marrow aspirates or bone morphogenic proteins (BMPs) to make up for its limitation [14][15][16]24]. Neen et al found that a collagenhydroxyapatite spongy with bone marrow aspirate showed equivalent fusion rate in posterolateral gutter but significantly lower fusion rate in interbody space than iliac bone graft, 83-93%.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that Healos ® is not an efficient bone graft substitute as lumbar spinal fusions are not achieved in adult New Zealand rabbits [30].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Data from animal studies would suggest that a bone graft substitute with some level of osteoinductivity is most effective for posterolateral spinal arthrodesis because it can combine the creeping substitution process of bone ingrowth from the decorticated host bone, with recruitment and differentiation of additional progenitor cells from the surrounding soft tissue adding a centripetal pattern of bone-healing 5,6 . Specific BMPs (BMP-2, 4, 6, 7, and 9) have demonstrated the potential for varying degrees of osteoinductivity 7 .…”
Section: Current Status Of Osteoinductive Agents For Spine Fusionmentioning
confidence: 99%